Proactive disaster notification: utilizing smart home networks for emergency response - Kountouri, Josefina; Tzouvaras, Marios; Panagiotou, Constantinos F.; Prodromou, Maria; Evagorou, Evagoras S.; Mettas, Christodoulos; Andreou, Chrysafis; Hadjimitsis, Diofantos G. (My University, 2025)
The increasing intensity and occurrence of natural disasters such as fires, earthquakes, and floods, necessitate the design of more effective emergency notification systems. Conventional alarm systems, such as sirens, and SMS alarms, are often insufficient to address issues such as slow response times and the provision of warnings of limited accuracy. By providing near real-time, localized notifications, a more proactive strategy that makes use of smart home technologies could improve disaster preparedness. This study focuses on the contribution of smart home environments to emergency alerting systems with Cyprus used as the pilot study. Cyprus is vulnerable to natural hazards, highlighting the need to develop more reliable and efficient warning technologies. Compared with traditional systems, the potential to develop a distributed alert system that increases the precision and promptness of warnings by utilizing sensors that are frequently present in smart homes, such as temperature, smoke, and flood monitoring, will be explored. Data will be collected from several households and used to evaluate the ability of the proposed concept to reduce false alarms while guaranteeing pertinent notifications. The feasibility of this approach is also discussed in terms of key design principles, challenges, and installation issues. The integration of this approach with existing emergency response frameworks, scalability, and user adoption is also considered since this is a crucial factor for the success of such systems. The outcomes of this analysis provide a foundation for further research and practical evaluation, contributing to broader discussion on how smart technologies can be leveraged for enhanced disaster resilience and public safety.
Keywords: Proactive disaster; smart home networks; emergency response